Self-Concept and Feeling of Belonging as a Predictor Variable of the Attitude towards the Study from the PISA 2018 Report - Nieves Gutiérrez; Isabel Mercader; José Juan Carrión; Rubén Trigueros (MDPI AG, 2022)
The importance of self-concept and the feeling of belonging to a school have been highlighted in numerous studies as predictors of school success. However, there are hardly any studies that link the relationship between self-concept and the feeling of belonging to the school. Thus, the aim of this study is to analyze the influence of personal and educational self-concept on the feeling of belonging to school, based on the data provided by the PISA 2018 report. To achieve this objective, a correlational methodology based on structural equation modelling has been used. The sample of participants is composed of 35,943 students of Compulsory Secondary Education from different Spanish high schools that participated in the PISA 2018 Report. The results obtained have shown that personal and educational self-concept correlate positively. In addition, both factors were positively related to the feeling of belonging to the educational centre. This study allows us to infer the idea of the existence of a direct and positive correlation between school and personal self-concept and the feeling of belonging, which would allow schools to develop educational intervention programmes with the aim of promoting the student's self-concept in order for them to feel better integrated into the school.